Epigenetic Alterations in Aging: A Brief Review - Ekowati, Ana Lucia; Milas Siswanto, Ferbian (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2024)
Background: Extensive studies have reported the involvement of epigenetic dynamics in aging. Common epigenetic modifications in aging include the methylation of DNA, rearrangement of chromatin, and regulation of gene expression by non-coding RNA (ncRNA). Some important conclusions that have emerged from various studies in the past few decades are that the lifespan of living organisms is largely determined by epigenetics instead of genetics, where environmental and lifestyle influences that change epigenetic information have a dominant effect. Purpose: This study aims to review current understanding of the mechanisms involved in epigenetic regulation during aging that would provide new insights for the development of strategies to prevent aging. Methods: A search for literature regarding epigenetic regulations in biological aging was carried out in Web of Science and Scopus on “epigenetics” [AND] “aging”. In this study, we used a total of 73 articles published between 2010 and 2024. Results: Aging is accompanied by various alterations in epigenetic marks, including DNA methylation (global hypomethylation in non-CpG regions and hypermethylation OF CpG islands), rearrangement of chromatin (global reduction of histones and redistribution of histone modifications), and ncRNA (particularly miRNA). Epigenetic is a reversible molecular mechanism that allow therapeutic interventions to improve or reverse aging-related pathogenesis. Chemical-based epigenetic manipulation and lifestyle-based epigenetic reprogramming strategies can be developed to improve or reverse aging-related conditions. Conclusion: Based on extensive literature review, we found that epigenetic changes are potential biomarkers for early detection of aging and age-related diseases. Drugs that target key epigenetic signatures are therefore promising to intervene aging. Keywords: aging - age-related disease - biomarker - epigenetic regulation